CRIMES AGAINST HUMANITY IN THE MODERN AGE - Sadat, Leila Nadya (The American journal of international law, 2013)
Sadat demonstrates that crimes against humanity charges will be equally as important at the International Criminal Court (ICC) as they have been at the ad hoc tribunals, both quantitatively and qualitatively. Moreover, crimes against humanity will often be the only offense chargeable in a particular case, as seen in the Libya situation, the Kenya situation and, for the time being, in Co'te d'Ivoire. Thus, the ICC, even more than the ad hoc tribunals, is largely going to be a "crimes against humanity" court. Successful prosecutions for crimes against humanity will be critical if the Court is to fulfill its mandate to punish the perpetrators of atrocity crimes; the possibility of such convictions will be critical if it is to fulfill its mandate to prevent.